Supramolecular Brake for Slowing Fentanyl Into Brain to Ameliorate Its Therapeutic Outcome - Longming Chen; Kaili Jiang; Yuanyuan Liu; Mengran Song; Yibo Zhao; Chengyang Tian; Yahan Zhang; Ziliang Zhang; Xiang Yu; Junhai Xiao; Junyi Chen; Zheng Yong; et al. (SmartMat, 2025)
ABSTRACT Fentanyl (Fen) analogs, clinically used anesthetic adjuvants, are often trouble with overdose‐induced adverse effects due to rapid entry into the brain plus short retention time. Advanced approaches that can relieve related life‐threatening symptoms without compromising their anesthetic efficacy are urgently needed to satisfy these special requirements. Herein, we propose that utilization of a well‐matched macrocycle, terphen[3]arene sulfate (TP3S) as a molecular‐level brake for Fen via the pharmacokinetic mode to execute this task. NMR and titration experiments confirm that TP3S possessed strong complexation ability toward Fen with an association constant of (1.36 ± 0.12) × 106 M−1. Then, Transwell assays demonstrate that TP3S itself is unable to cross the blood–brain barrier, and codosed with Fen could effectively decelerate its velocity of entering the brain. Respiration‐related evaluations and pharmacodynamics analyses reveal that administration of such a brake alleviates Fen‐induced respiratory depression without losing its effectiveness. The therapeutic index of Fen/TP3S is calculated to be ~57% higher than that of Fen alone, and through pharmacokinetic studies, it has been clarified that ameliorating Fen's therapeutic outcome stemmed from reducing the initial brain concentration of Fen and maintaining its effective dose for a longer time. This supramolecular approach could also act on other opioids as long as strong binding was achieved.